Gordey Maksimovich Iosifov (to the 140 anniversary) - L. V. Saveliyeva; L. A. Grigoriyeva; R. V. Danilchuk; N. M. Melchikova (Бюллетень сибирской медицины)
Submitted biography of professor Gordey Maksimovich Iosifov — founder of the national lymphology, head of the chair of normal anatomy of the Imperial Tomsk University has been presented.